Mitigating the Impact of Violence Against Children in Pondok Pesantren in East Java: Strengthening Human Resources in Anticipating Child Abuse - Titik Triwulan Tutik; Agus Aditoni; Zainatul Ilmiyah (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2026)
Violence against children remains a critical global issue with significant social, psychological, and legal implications for educational institutions. In Indonesia, Islamic boarding schools (pondok pesantren) face increasing scrutiny as cases of neglect, psychological abuse, and physical violence emerge amidst limited supervisory and reporting mechanisms. This community service project (pengabdian kepada masyarakat) aims to strengthen the awareness and capacity of pesantren human resources (HR)—including kiai, pengasuh, school managers, ustadz, and ustadzah (teachers), as well as student mentors—to anticipate and mitigate child abuse within educational environments. Activities were conducted in Malang, Kediri, and Blitar Regencies through Focus Group Discussions (FGDs), interviews, deliberative forums, and dialogic workshops. In Malang, 25 participants from 11 pesantren across five sub-districts participated, while in Kediri–Blitar, 30 participants from five sub-districts attended the sessions. This article presents the conceptual framework, methodological approach, empirical findings, and implications for institutional strengthening. The study concludes that increasing HR awareness, training in early detection, establishment of standard operating procedures (SOPs), and multi-stakeholder collaboration are essential strategies for mitigating violence against children in pesantren.